2012
DOI: 10.3168/jds.2012-5582
|View full text |Cite
|
Sign up to set email alerts
|

Cow and herd variation in milk urea nitrogen concentrations in lactating dairy cattle

Abstract: Milk urea nitrogen (MUN) is correlated with N balance, N intake, and dietary N content, and thus is a good indicator of proper feeding management with respect to protein. It is commonly used to monitor feeding programs to achieve environmental goals; however, genetic diversity also exists among cows. It was hypothesized that phenotypic diversity among cows could bias feed management decisions when monitoring tools do not consider genetic diversity associated with MUN. The objective of the work was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 37 publications
2
34
1
6
Order By: Relevance
“…This was the case in our study, as well. However, mean MY in our study was similar (Arunvipas et al, 2003;Nousiainen et al, 2004) or lower (Godden et al, 2001b;Johnson and Young, 2003;Hojman et al, 2004;Aguilar et al, 2012;Fatehi et al, 2012;Doska et al, 2012) than what has been reported in other MUN studies. Other parameters must also be considered.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…This was the case in our study, as well. However, mean MY in our study was similar (Arunvipas et al, 2003;Nousiainen et al, 2004) or lower (Godden et al, 2001b;Johnson and Young, 2003;Hojman et al, 2004;Aguilar et al, 2012;Fatehi et al, 2012;Doska et al, 2012) than what has been reported in other MUN studies. Other parameters must also be considered.…”
Section: Resultscontrasting
confidence: 55%
“…Greater variance (22.7-42%) was found by Johnson and Young (2003), Nousiainen et al (2004), Bastin et al (2009), Aguilar et al (2012), Fatehi et al (2012) and Doska et al (2012).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…El contenido de NUL puede verse afectado por muchas otras variables como etapa de lactancia, número de partos y temperatura ambiental (Fatehi & Young 2012), efecto individual de hato y de vaca (Aguilar et al 2012) y genética de los animales (Mucha & Strandberg 2011), por lo que, nuevamente, su empleo en la toma de decisiones e intervenciones debe hacerse tomando las precauciones del caso.…”
Section: Aspectos Teóricosunclassified
“…This may also apply to measuring hydration status in neonatal calves. The mixed model of (Aguilar et al, 2012) demonstrates how milk urea nitrogen (mg/dL) in multiparous Holstein and Holstein-cross-Jersey cows is partly explained by cow milk yield (kg/d) and cow crude protein intake (kg/d), with respective parameter estimates of -0.33 and 20.3. Therefore, in neonatal calves, the negative association between plasma urea concentration and hydration may be partly confounded, if there is a positive association between plasma urea concentration and milk uptake.…”
Section: Observing and Quantifying Hydration Status In Neonatal Calvesmentioning
confidence: 99%